Microwave‐Assisted Synthesis of C‐4′‐(1, 5‐disubstituted)‐triazole‐spiro‐α‐L‐arabinofuranosyl Nucleosides. Issue 26 (12th September 2017) - Rungta, Pallavi; Mangla, Priyanka; Maikhuri, Vipin K.; Singh, Sunil K.; Prasad, Ashok K.
Abstract: The synthesis of C ‐4′‐(1, 5‐disubstituted)‐triazole‐spiro‐ α ‐L‐arabinofuranosyl nucleosides has been achieved in a regio‐ and stereospecific manner by using intramolecular Huisgen 1, 3‐dipolar cycloaddition reaction. The synthesis of these nucleosides necessitates the possession of azide and alkyne moieties in the same molecule, which is being employed as the precursor. Thus, the crucial step in the synthesis of targeted compound is the preparation of 1, 2, 3‐tri‐ O ‐acetyl‐5‐azido‐5‐deoxy‐4‐ C ‐propynyl‐ α, β ‐L‐arabinofuranose and its conversion to corresponding nucleosides via nucleobase coupling. The microwave heating of such tailor made nucleoside precursors furnishes the targeted spironucleosides, which combines conformational‐restriction concept with a triazole structural feature highly sought in drug design. Abstract : Intramolecular Huisgen 1, 3‐dipolar cycloaddition reaction under microwave conditions yielded the desired C ‐4′‐(1, 5‐disubstituted)‐triazole ‐ spiro‐ α ‐L‐arabinofuranosyl nucleosides. These nucleosides are locked in a particular conformation. Such modified nucleosides demand a key precursor containing both azide and alkyne moities in the same unit which can be achieved by carrying out chemical transformations on D‐glucose.